2022
DOI: 10.5194/bg-19-2333-2022
|View full text |Cite
|
Sign up to set email alerts
|

Changing sub-Arctic tundra vegetation upon permafrost degradation: impact on foliar mineral element cycling

Abstract: Abstract. Arctic warming and permafrost degradation are modifying northern ecosystems through changes in microtopography, soil water dynamics, nutrient availability, and vegetation succession. Upon permafrost degradation, the release of deep stores of nutrients, such as nitrogen and phosphorus, from newly thawed permafrost stimulates Arctic vegetation production. More specifically, wetter lowlands show an increase in sedges (as part of graminoids), whereas drier uplands favor shrub expansion. These shifts in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 115 publications
1
7
0
Order By: Relevance
“…Betula nana was found to increase near‐surface long‐lived fine root biomass in a fertilization experiment (Sullivan et al, 2007), which could partially explain its successful eventual replacement of E. vaginatum (which has an annual root system) in long‐term Arctic fertilization experiments (Shaver and Chapin, 1995; Shaver et al, 2001). Recent studies have suggested that initial uptake of nutrients by fast‐growing graminoids and other deeply rooted forbs may move nutrients above‐ground in the form of more quickly decomposing litter, where shrubs may then access it over longer time‐scales (Wookey et al, 2009; Hewitt et al, 2019; Mauclet, Agnan, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Betula nana was found to increase near‐surface long‐lived fine root biomass in a fertilization experiment (Sullivan et al, 2007), which could partially explain its successful eventual replacement of E. vaginatum (which has an annual root system) in long‐term Arctic fertilization experiments (Shaver and Chapin, 1995; Shaver et al, 2001). Recent studies have suggested that initial uptake of nutrients by fast‐growing graminoids and other deeply rooted forbs may move nutrients above‐ground in the form of more quickly decomposing litter, where shrubs may then access it over longer time‐scales (Wookey et al, 2009; Hewitt et al, 2019; Mauclet, Agnan, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach has been successfully used in western Siberia (Frey and Smith, 2005) to model the possible future changes in small (Krickov et al, 2018) and medium-size rivers, lakes (Manasypov et al, 2022), soil waters (Raudina et al, 2018) and permafrost ice (Lim et al, 2021). Indeed, with permafrost boundary shift northward (Romanovsky et al, 2010) and tundra greening over next decades as it is observed generally through the Arctic and subarctic regions (Tape et al, 2006;Garcia Criado et al, 2020;Mauclet et al, 2022), the northern part of the Taz River (tundra and forest-tundra of continuous to discontinuous permafrost) can be entirely transformed into southern part-like territory of taiga and forest-tundra biome with discontinuous to sporadic permafrost. Given that the CO 2 flux in the upper (southern) 400 km of the river main stem and tributaries is a factor of 2-3 higher than that in the lower (northern) part of the basin, one can expect a 2 to 3-fold increase in the CO 2 emission from the Taz River basin due to on-going climate warming and permafrost thaw.…”
Section: Carbon Evasion Compared To Lateral Export Of Riverine Carbon...mentioning
confidence: 99%
“…Such an approach has been successfully used in western Siberia since the pioneering work of Frey and Smith [12] to model possible future changes in small rivers [13,59], lakes [61], soil waters [23], and permafrost ice [21]. Indeed, with permafrost and forest boundary shift northward over next decades [9,[63][64][65], the northern part of the Taz River (tundra and forest-tundra of continuous to discontinuous permafrost) can be entirely transformed into southern part-like territory of taiga and forest-tundra biome with discontinuous to sporadic permafrost, whereas the entire Ket River basin can be used as a surrogate for hydrochemistry for the southern part of the Taz River. The mean element concentrations in the main stem and tributaries in the two subbasins of the Taz and Ket River are illustrated in Figure 8.…”
Section: Common Features Of Spatial Distribution Of Major and Trace E...mentioning
confidence: 99%